2013
DOI: 10.1007/s00586-013-2896-0
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of depressive symptoms before and after surgery and its association with disability in patients undergoing lumbar spinal fusion

Abstract: One-third of our patients with chronic back pain undergoing spinal fusion had depressive symptoms pre-operatively. The prevalence of depressive symptoms decreased after surgery. Although disability remained higher in those patients who had reported depressive symptoms pre-operatively, disability did decrease significantly in both groups post-operatively. Thus, there is no need to exclude depressive patients from operation, but screening measures and appropriate treatment practises throughout both pre-operative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 27 publications
3
45
0
Order By: Relevance
“…Depressive symptoms have been shown to predict poorer surgical outcome after lumbar spine surgery [29][30][31][32][33], which finding is in accordance with our observation. To our knowledge, this is the first study to examine the role that different depression subtypes play in modifying the postoperative result after spinal surgery.…”
Section: Discussionsupporting
confidence: 95%
“…Depressive symptoms have been shown to predict poorer surgical outcome after lumbar spine surgery [29][30][31][32][33], which finding is in accordance with our observation. To our knowledge, this is the first study to examine the role that different depression subtypes play in modifying the postoperative result after spinal surgery.…”
Section: Discussionsupporting
confidence: 95%
“…Patients living alone had more pain, which might be explained by the lack of disease-related support. There are similar reports involving other orthopedic conditions where psychological factors have affected the perception of pain (Wahlman et al 2014). Also, in shoulder complaints several psychological factors have been related to outcome (Bot et al 2005).…”
Section: Discussionsupporting
confidence: 63%
“…19 In another study of 232 patients who had undergone instrumented lumbar spine fusion, the authors noted that 32% of patients had preoperative depression symptoms but only 15% had them at the 1-year follow-up. 25 These researchers concluded that the prevalence of depressive symptoms decreased after surgery. Disability remained higher in patients who had reported depressive symptoms preoperatively but decreased significantly after surgery; thus, the authors suggested that there was no need to exclude depressive patients from surgery, although screening measures and appropriate treatment practices were encouraged.…”
Section: -19mentioning
confidence: 99%
“…1,2,[16][17][18][19][20]23,25 To our knowledge, there is no information in the literature concerning the influence of depression symptoms on patient expectations. We hypothesized that patient expectations can be affected by depression symptoms and, consequently, will affect clinical results.…”
mentioning
confidence: 99%